Carbon for the oxygen reduction reaction: a defect mechanism1. Issue 22 (14th June 2015) - Zhao, Huanyu; Sun, Chenghua; Jin, Zhao; Wang, Da-Wei; Yan, Xuecheng; Chen, Zhigang; Zhu, Guangshan; Yao, Xiangdong
<x xml:space="preserve">Abstract</x> A new defect mechanism for the ORR was proposed based on the theoretical calculations and our experimental results.